Introduction to Radiobiology of Targeted Radionuclide Therapy - Pouget, Jean-Pierre; Lozza, Catherine; Deshayes, Emmanuel; Boudousq, Vincent; Navarro-Teulon, Isabelle (Frontiers in Medicine, 2015)
During the last decades, new radionuclide-based targeted therapies have emerged as efficient tools for cancer treatment. Targeted radionuclide therapies (TRT) are based on a multidisciplinary approach that involves the cooperation of specialists in several research fields. Among them, radiobiologists investigate the biological effects of ionizing radiation, specifically the molecular and cellular mechanisms involved in the radiation response. Most of the knowledge about radiation effects concerns external beam radiation therapy (EBRT) and radiobiology has then strongly contributed to the development of this therapeutic approach. Similarly, radiobiology and dosimetry are also assumed to be ways for improving TRT, in particular in the therapy of solid tumors which are radioresistant. However, extrapolation of EBRT radiobiology to TRT is not straightforward. Indeed, the specific physical characteristics of TRT (heterogeneous and mixed irradiation, protracted exposure and low absorbed dose rate) differ from those of conventional EBRT (homogeneous irradiation, short exposure and high absorbed dose rate), and consequently the response of irradiated tissues might be different. Therefore, specific TRT radiobiology needs to be explored. Determining dose-effect correlation is also a prerequisite for rigorous preclinical radiobiology studies because dosimetry provides the necessary referential to all TRT situations. It is required too for developing patient-tailored TRT in the clinic in order to estimate the best dose for tumor control, while protecting the healthy tissues, thereby improving therapeutic efficacy. Finally, it will allow to determine the relative contribution of targeted effects (assumed to be dose-related) and non-targeted effects (assumed to be non-dose-related) of ionizing radiation. However, conversely to EBRT where it is routinely used, dosimetry is still challenging in TRT. Therefore, it constitutes with radiobiology, one of the main challenges of TRT.